The Impact of Spondyloarthritis and Joint Symptoms on Health-Related Quality of Life and Fatigue in IBD Patients. Results From a Population-Based Inception Cohort (20-Year Follow-up in the Ibsen Study). Issue 1 (25th May 2019) - Ossum, Alvilde Maria; Palm, Øyvind; Cvancarova, Milada; Bernklev, Tomm; Jahnsen, Jørgen; Moum, Bjørn; Høivik, Marte Lie; ,
Abstract : Ongoing joint pain and back pain were associated with reduced quality of life and fatigue in IBD patients after 20 years of disease, whereas spondyloarthritis without ongoing joint symptoms did not have a negative impact on these patient-reported outcomes. Abstract: Background: Patients with inflammatory bowel disease (IBD) often suffer from musculoskeletal manifestations. Health-related quality of life (HRQoL) and fatigue are known to be associated with IBD activity and musculoskeletal complaints. The aim of this study was to determine the association between spondyloarthritis, arthralgia, or back pain and the patient-reported outcomes of HRQoL and fatigue in IBD patients 20 years after their diagnosis. Methods: The IBSEN cohort was followed prospectively for 20 years. At the 20-year follow-up, the patients answered detailed questionnaires regarding rheumatological manifestations, intestinal symptoms, HRQoL, and fatigue. Multiple regression analyses were used to evaluate associations between spondyloarthritis or joint symptoms and HRQoL or fatigue. Sex, IBD diagnosis, and age were included in all the multiple regression models, in addition to other clinically relevant confounders. Results: In total, 441 patients (94%) completed the questionnaires at the 20-year follow-up. The criteria for spondyloarthritis (axial or peripheral) were fulfilled in 158 patients (36%), current back pain during the previous 3 months was reported by 79 patients (18%), and current arthralgia was reported by 178 patients (40%). Current back pain and arthralgia were independently associated with lower HRQoL, higher levels of fatigue, and chronic fatigue. A diagnosis of spondyloarthritis was not associated with reduced HRQoL or fatigue when adjusted for possible confounders. Conclusions: Current joint symptoms in IBD patients 20 years after diagnosis were associated with poorer HRQoL, higher levels of fatigue, and chronic fatigue, whereas spondyloarthritis did not impact HRQoL or fatigue negatively in this cohort.